Effect of Alleviating Preoperative Anxiety on Gastrointestinal Function Recovery After Laparoscopic High Ligation of the Hernia Sac in Children with Indirect Inguinal Hernia - Chen X; Zhang X; Gao R; Huang Y; Mao S; Wang B; Feng J (Dove Medical Press, 2024)
Xinyue Chen,1 Xue Zhang,2 Ruijia Gao,2 Yu Huang,3 Shimeng Mao,2 Bing Wang,4 Jiying Feng4 1Department of Anesthesiology, Jinzhou Medical University, Jinzhou, Liaoning, People's Republic of China; 2Department of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 3Department of Anesthesiology, Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China; 4Department of anesthesiology, the Affiliated Lianyungang Hospital of Xuzhou Medical University, the First People's Hospital of Lianyungang, Lianyungang, Jiangsu, People's Republic of ChinaCorrespondence: Jiying Feng, No. 6 East Zhenhua Road, The Affiliated Lianyungang Hospital of Xuzhou Medical University, Lianyungang, Jiangsu, People's Republic of China, Email fengjymz@163.comPurpose: Anxiety and depression can affect the physiology of the gastrointestinal tract through the brain-gut axis, causing gastrointestinal dysfunction, which is mainly manifested as indigestion, diarrhoea, constipation, or abdominal pain. Preoperative anxiety arises in children due to separation from parents, fear of unfamiliar surroundings and anaesthesia and surgical procedures.To discuss the effect of alleviating preoperative anxiety on postoperative recovery of gastrointestinal function in children with indirect inguinal hernia after laparoscopic high ligation of the hernia sac.Patients and Methods: 90 children with laparoscopic high ligation of the herniated sac in oblique inguinal hernia were randomly divided into control group (Group C) and experimental group (Group M). The Group M was given midazolam oral solution 0.5mg/kg (maximum dose 20mg), and The Group C was given 5% glucose solution with the same dose.Primary outcome was the time to first postoperative defecation and I-FEED scores.The secondary outcomes included mYPAS-SF scores; child sedation scores; child-parent separation scores; parental STAI scores;PHBQ scores;FLACC scores, operative time, and fluid input and surgeon job satisfaction.Results: Compared with Group C, there was a shorter time to first postoperative defecation (P < 0.05), and lower I-FEED scores on postoperative day 1 (P < 0.05). The mYPAS-SF scores, which were significantly different in Group M at T1, T2, and T3 (P < 0.05), parental STAI scores at S1, child sedation scores and child-parent separation scores in T1, and surgeon job satisfaction between the two groups were significantly different (P < 0.05). There were no statistically significant differences in I-FEED scores on days 2 and 3, PHBQ scores, FLACC scores, operative time, and fluid input between the two groups of children (P > 0.05).Conclusion: Preoperative application of midazolam oral solution to relieve preoperative anxiety helps to promote the recovery of postoperative gastrointestinal function in children with indirect inguinal hernia and increases the surgeon job satisfaction.Keywords: preoperative anxiety, gastrointestinal function, midazolam:pediatric surgery